Pseudomonas putida UW4 producing ACC deaminase is a potential biocontrol agent for pine wilt disease - Nascimento, Francisco (2013)
Pine wilt disease, caused by the nematode Bursaphelenchus xylophilus, is responsible for devastation of pine forests worldwide. Until now, there are no effective ways of dealing with this serious threat. The use of ACC deaminase-producing plant growth promoting bacteria has been shown to be a useful strategy to reduce the damage due to biotic and abiotic stresses. Pinus pinaster seedlings inoculated with the ACC deaminase-producing bacterium Pseudomonas putida UW4 strain showed an increased root and shoot development and reduction of B. xylophilus induced symptoms. In contrast, P. putida UW4 ACC deaminase mutant was unable to promote pine seedling growth or to decrease B. xylophilus induced symptoms. This is the first report of the use of ACC deaminase-producing bacteria as a potential biological control agent for tree diseases, thus, suggesting that the inoculation of pine seedlings grown in a tree nursery might constitute a novel strategy to obtain B. xylophilus resistant pine trees.